Spatial Distribution of Shrubs Impacts Relationships among Saltation, Roughness, and Vegetation Structure in an East Asian Rangeland - Akito Kono; Toshiya Okuro (Land, 2021)
Vegetation influences the occurrence of saltation through various mechanisms. Most previous studies have focused on the effects of vegetation on saltation occurrence under spatially homogeneous vegetation, whereas few field studies have examined how spatially heterogeneous cover affects saltation. To examine how spatial heterogeneity of vegetation influences saltation, we surveyed the vegetation and spatial distribution of shrubs and conducted roughness measurements at 11 sites at Tsogt-Ovoo, Gobi steppe of Mongolia, which are dominated by the shrubs Salsola passerina and Anabasis brevifolia. Saltation and meteorological observations were used to calculate the saltation flux, threshold friction velocity, and roughness length. The spatial distribution of shrubs was estimated from the intershrub distance obtained by calculating a semivariogram. Threshold friction velocity was well explained by roughness length. The relationships among roughness, saltation flux, and vegetation cover depended on the spatial distribution of shrubs. When the vegetation was distributed heterogeneously, roughness length increased as the vegetation cover decreased, and the saltation flux increased because the wake interference flow became dominant. When the vegetation was spatially homogeneous, however, the saltation flux was suppressed even when the vegetation cover was small. These field experiments show the importance of considering the spatial distribution of vegetation in evaluating saltation occurrence.